Synthetic Analysis of Hidrograf Units using the Method of HSS Nakayasu, Snyder And Limantara (Study in DAS Way Sulan) - Haryadi Haryadi; Aprizal Aprizal; A Nurhasanah (International Conference on Engineering and Technology Development (ICETD), 2017)
DAS Way Sulan located in East Lampung Regency of Lampung Province. DAS Way Sulan this was the area of review in the research of the preparation of this thesis. Flood-prone areas in the planning area includes the  rea of the estuary's Way Home, flood plains and alluvial plain especially along the Way Sulan. Factors cause flooding include the high rainfall, the closure of land upstream capacity and reduced flow of the rivers especially in areas of lower reduced due to sedimentation and topographic area. Flood hazards/safeguards for potential flooding in River Way Sulan can do planning safeguards against a flood with a building plan that aims to reduce the damage that occurs due to the flood levels most minimum. Building planning in the field of water resources can be done well if rainfall data at each station the rain can be known and calculated using the debitnya method of the HSS